THE EFFECT OF THE WORD „FREE“ ON DIFFERENT GENERATIONS (Perner's Contacts, 2022)
In transportation, communications, or any other field, people often make decisions that are not rational. One influence that causes this is to offer something for free. This article aimed to investigate this influence between different generations. The aim was to find out if the younger generations react in a different way from the older generations. A significant difference was not found. However, in researching this problem, another phenomenon was shown (and confirmed), namely the influence of the wording of the offer with the word free.
Keywords: irrational behaviour; decision making; transportation; communications; free of charge; generations